2023
DOI: 10.7759/cureus.35120
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Colchicine on Atrial Fibrillation: A Systematic Review and Meta-Analysis

Abstract: Colchicine is a potent anti-inflammatory agent whose benefits have been explored for various conditions, including atrial fibrillation (AF). In this article, we tried to understand why colchicine might be beneficial in AF and reviewed various studies that looked at the effect of colchicine against AF. We followed the PRISMA algorithm and undertook a literature search to identify studies with control groups that looked at the effect of colchicine against AF and conducted a meta-analysis. We identified six studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…It demonstrated a reduced risk of recurrence over a 12-month period. 84 Whilst not in the same class of drugs, vinorelbine is a chemotherapeutic agent that acts by the inhibition of tubulin which is encoded by the same target TUBB3 . An RCT comparing vinorelbine combined with gemcitabine vs gemcitabine alone in patients with stage III or IV non-small cell lung cancer demonstrated a higher rate of incident AF.…”
Section: Resultsmentioning
confidence: 99%
“…It demonstrated a reduced risk of recurrence over a 12-month period. 84 Whilst not in the same class of drugs, vinorelbine is a chemotherapeutic agent that acts by the inhibition of tubulin which is encoded by the same target TUBB3 . An RCT comparing vinorelbine combined with gemcitabine vs gemcitabine alone in patients with stage III or IV non-small cell lung cancer demonstrated a higher rate of incident AF.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, they found out that the incidence of major adverse events was not increased (RR: 0.86; 95% CI, 0.46–1.60; P = 0.64) in the colchicine arm indicating the relative safety of colchicine among patients who underwent cardiothoracic surgery. Looking at cardiac surgery alone, Kommu et al 19 established colchicine was beneficial against POAF (RR: 0.70; 95% CI, 0.58–0.84; P < 0.001). In this study, they included patients who underwent catheter-based procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine may prevent atrial fibrillation with different anti-inflammatory mechanisms: inhibition of IL-6 release and consequent fibrosis; activation of the PI3K/AKT/eNOS signalling pathway, which may reverse atrial remodelling; and reduction of NLRP3 inflammasome activity. [42][43][44] A recent meta-analysis 45 evaluated the use of colchicine in preventing atrial fibrillation in three different settings: postoperative atrial fibrillation (POAF) after cardiac surgery, atrial fibrillation recurrence following pulmonary vein ablation/isolation, and atrial fibrillation in patients with CAD. The meta-analysis found that colchicine is beneficial in decreasing the incidence of POAF, with a relative risk of 0.7 (95% CI 0.58-0.84).…”
Section: Atrial Fibrillationmentioning
confidence: 99%